New Chemical Grouting Materials and Rapid Construction Technology for Inclined Shaft Penetrating Drift-Sand Layer in Coal Mine - Xicai Gao; Xinyu Wang; Xiangdong Liu (Advances in Materials Science and Engineering, 2018)
Drift-sand layer is a common weak stratum in mine construction. The construction of the shaft passing over the drift-sand layer is very difficult. Traditional construction method faces many problems such as long construction period, high construction cost, poor working environment, and uncontrollability of the support effect. In view of the loose and fragile rock mass with great deformation of sinking and driving engineering penetrating drift-sand layers in coal mine, the reaction mechanism and shortcomings of conventional chemical grouting materials were analyzed. New-type polymer grouting materials were prepared with catalysts and vinyl epoxy resin, which was made from epoxy resin. A comprehensive chemical grouting construction technology was proposed, which comprises initiative closing, concentrated bypass flow, water plugging priority, and secondary sand curing for the inclined shaft passing over the drift-sand layer. Results show that new-type polymer sand-cured materials have lower viscosity, better grout ability, and fire resistance, and the solidified material has stronger bonding strength and better deformation resistance compared with traditional chemical grouting materials. The engineering application effect is very prominent in controlling water burst and leakage at the drift-sand layer; thus the on-site comprehensive construction progress and safety are guaranteed.